Query recovery attacks against conjunctive keyword searchable encryption - DU Ruiying; SHEN Bei; HE Kun; ZHAO Chenbin; WANG Beining; CHEN Jing (Tongxin xuebao)
In order to recover user’s queries in conjunctive keyword searchable encryption schemes, two attacks against the conjunctive keyword searchable encryption schemes were proposed, such as cross leakage attack and frequency matching attack. Firstly, a set of candidate keywords were extracted from the leakage. Then the keywords were filtered according to the keyword pair result pattern leakage and query frequency information respectively. Results show that in the cross leakage attack, with knowledge of only 10% of the dataset, the accuracy of query recovery can reach up to 90% if the keyword space is 100. And more than 50% of the queries are still able to recovered by the attacker if the keyword space is expanded to 1 000. In frequency matching attack, even with only inaccurate frequency distribution information known to the attacker, at least 70% of queries can be accurately recovered.